(untitled) (Experimental biology, 2022)
Interest in bioethanol has grown significantly in recent decades, not only as a solvent, antifreeze or feedstock for the production of a wide range of different organic compounds, but also, to some extent, as a biofuel. Bioethanol has the following advantages over gasoline: it is less polluting, decomposes easily, has a high octane number, and can use renewable raw materials for its production. The ever-growing demand for bioethanol requires the search for new substrates that are cheaper than grain or potatoes. As one of these substrates, it is recommended to use whey, the main carbohydrate of which is lactose. The purpose of the study: to study the microbiological indicators and taxonomic composition of the microbial community of whey. In the course of the study, the microbiological indicators and taxonomic composition of the microbial community of whey of Merke Cheese Factory LLP, Amiran LLP (whey), Stella Alpina LLP (cheese whey) were studied. From the serum samples, 3 strains of yeast and 1 strain of lactic acid bacteria were isolated. As a result of prespecies identification of cultures of yeasts and lactic acid bacteria, strains of GB and GT were identified as Kluyveromyces marxianus, strain M1 - Lactococcus lactis, A1 - Candida inconspicua. Key words: whey, bioethanol, yeast cultures, lactic acid bacteria, strain.